2013
DOI: 10.1159/000348662
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Quality Control: Impact on Aging and Life Span - A Mini-Review

Abstract: A fundamental impact of mitochondria on biological aging has been suggested decades ago. One prominent theory explains aging as the result of the age-related accumulation of random molecular damage of biomolecules resulting from the reaction of reactive oxygen species, the majority of which are generated in mitochondria. Although this concept appeared to be very attractive and strongly influenced aging research, in recent years more and more data accumulated which seem to contradict this theory. However, since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…In the past, we have demonstrated a number of different pathways to be part of such a network to affect aging and life span control in P. anserina (reviewed in refs. 8, 69, and 70). Until now, we had no experimental evidence for such an impact of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, we have demonstrated a number of different pathways to be part of such a network to affect aging and life span control in P. anserina (reviewed in refs. 8, 69, and 70). Until now, we had no experimental evidence for such an impact of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…CLPP plays a role in the mitochondrial unfolded protein response pathway (mtUPR) by multimerizing with the CLPX chaperone within the mitochondrial matrix, thereby forming a proteasome-like cylinder that is capable of hydrolyzing mitochondrial proteins into small peptides. It is therefore expected to react upon protein conformational stress in mitochondria by inducing mitochondrial stress signaling pathways (17, 18). Molecular characterization of Clpp null mice has demonstrated that the absence of Clpp transcripts leads to significant increases in mtDNA copy number in several tissues (testis, ovary, heart, and brain) (15).…”
Section: Discussionmentioning
confidence: 99%
“…This observation supports an epistatic interaction between mitochondrial inner membrane stress and cytosolic protein homeostasis in the control of replicative lifespan. A role of mitochondria in aging and lifespan control is well established [91, 92]. It has been extensively documented that adaptive mitochondria-to-nucleus signaling via the retrograde-response pathway increases cell's lifespan (for review, see [93]).…”
Section: Ant Mutations Induce Degenerative Cell Deathmentioning
confidence: 99%